Features of Production Resource Management in the Networked Economy - Mansur F. SAFARGALIEV; Alexander P. SNEGURENKO; Roman E. MOISEEV; Ruslan F. GARIFULLIN (Communications of International Proceedings, 2021)
The article formulates the principles of resource management for innovative activities in network production systems, such as a) separation of information, financial, personnel and material and technical flows in the interaction of business entities and resource suppliers by including it the interacting scheme a range of additional participants ensuring the guaranteed flow of individual flows; b) a principle of polyresource capacity and interchangeability of created products for facilitated network migration of manufacturers and consumers between suppliers of different resources types; c) a principle of advanced scientific and technical development of resource providers and network executors of innovative projects, which automatically introduce new solutions and technologies into the network production system that accelerate the dynamics of network development due to progressive requirements for network participants in the field of updating parameters and conditions of their innovative activity. The application of the principles makes it possible to increase the reliability of interaction and the stability of the organizational and resource support of innovative activities in networked production systems, to increase the rate of technology updating due to the use of organizational resources of the external environment, proactive setting of higher standards of interaction, as well as increasing the mobility of production.
Keywords: Networked Economy; Manufacturing; Multiservice; Uberization; Advanced Development.